Phytoremediation Mechanisms of Lead (Pb) Metal Contaminated Soils of some location in Baghdad City - Huda Farooq Zaki (Journal of Global Pharma Technology, 2018)
Mechanisms phytoremediation of Lead metal from contaminated soil are a little time consuming because metals cannot degrade, therefore effective cleanup requires  to reduce or remove toxicity, use of plants to remove, detoxify or immobilize environmental contaminants in a growth matrix in soil  through the natural, biological, chemical or physical activities or processes of some location in Baghdad city , the current study was conducted to determine the effects of soil pollution on the elements and the plant absorption of pollutants and their effect on the population in parks, In the city of Baghdad, where ten areas were identified (5 areas by Karkh - 5 areas of the Rusafa side with control), pH and soil tissue were measured and element concentrations (pb) through the average results of plants that have been obtained there is a relationship between plants with a difference from one to other depending on the ability to absorb Lead and content in three dominate plants species, Consecutively: Cynodon dactylon> Eucalyptus camaldulensis> Dodonea viscosa,( 0.033, 0.032. 0.018) Respectively. Lead compounds can be dissolved in water which may result in introduction to soil and thus transfer to food chain. Many industrial activities such as mining, processing minerals and chemical industries, increase non-essential metal concentration in the water tables in the surrounding regions of their manufacturing plants.